Asosiasi gastropoda di ekosistem padang lamun Perairan Senggarang Besar, Kepulauan Riau, Indonesia - Fajeri; Febrianti Lestari; Susiana (Sekolah Tinggi Ilmu Pertanian Wuna, 2020)
This study aims to determine the type and density of gastropods, the density of seagrass, seagrass closure. It also knows the association gastropods in seagrass ecosystem in the waters of the Senggarang Besar. The research was conducted by random sampling method using a point 31 transect squares measuring 1x1 meters for observation gastropods and seagrass. Results of the study were found 12 species of gastropods. Gastropod density values range between 0.35-2.94 individual/m2. Results of research on the type of seagrass found 4 species of seagrass that is, Enhalus acoroides, Thalassia hemprichii, Halodule uninervis and Syringodium isoetifolium. A density value of seagrass species Enhalus acoides 14.32 individual/m2, Thalassia hemprichii 86.39 individual/m2, Halodule uninervis 21.58 individual/m2 and Syringodium isoetifolium 3.87 individual/m2. Total density of all seagrass 126.16 individual/m2. The closure of the Seagrass Enhalus acoides 12,63%, Thalassia hemprichii 50,96%, Halodule unnerves 13,40% and Syringodium isotifolium 0.29%. Total closure of all seagrass is 77,29%. The level of association between species of gastropods as many as 11 species have negative associations of which is Leavistrombus turturela, Strombus urceus, Planaxis sulcatus, Cerithium nesioticum, Cerithium Aluco, Cerithium zonatum, Pugilina cocholidium, Cronia margariticola, Muricodrupa fiscela, Pyrene epamella, Otopleura auriscati. While 1 species has a positive association level is kind of Rhinoclavis aspera.